Comparison of ozone profiles from DIAL, MLS, and chemical transport model simulations over Río Gallegos, Argentina, during the spring Antarctic vortex breakup, 2009 - Sugita, Takafumi (2017)
This study evaluates the agreement between ozone profiles derived from the ground-based differential absorption lidar (DIAL), satellite-borne Aura Microwave Limb Sounder (MLS), and 3-D chemical transport model (CTM) simulations such as the Model for Interdisciplinary Research on Climate (MIROC-CTM) over the Atmospheric Observatory of Southern Patagonia (Observatorio Atmosférico de la Patagonia Austral, OAPA; 51.6°S, 69.3°W) in Río Gallegos, Argentina, from September to November 2009. In this austral spring, measurements were performed in the vicinity of the polar vortex and inside it on some occasions; they revealed the variability in the potential vorticity (PV) of measured air masses. Comparisons between DIAL and MLS were performed between 6 and 100hPa with 500km and 24h coincidence criteria. The results show a good agreement between DIAL and MLS with mean differences of ±0.1ppmv (MLS-´DIAL, n,=-) between 6 and 56hPa. MIROC-CTM also agrees with DIAL, with mean differences of ±0.3ppmv (MIROC-CTM-´DIAL, n,=-23) between 10 and 56hPa. Both comparisons provide mean differences of 0.5ppmv (MLS) to 0.8-0.9ppmv (MIROC-CTM) at the 83-100hPa levels. DIAL tends to underestimate ozone values at this lower altitude region. Between 6 and 8hPa, the MIROC-CTM ozone value is 0.4-0.6ppmv (5-8%) smaller than those from DIAL. Applying the scaled PV (sPV) criterion for matching pairs in the DIAL-MLS comparison, the variability in the difference decreases 21-47% between 10 and 56hPa. However, the mean differences are small for all pressure levels, except 6hPa. Because ground measurement sites in the Southern Hemisphere (SH) are very sparse at mid-to high latitudes, i.e., 35-60°S, the OAPA site is important for evaluating the bias and long-Term stability of satellite instruments. The good performance of this DIAL system will be useful for such purposes in the future.